Linking ecosystem service supply to stakeholder concerns on both land and sea: An example from Guánica Bay watershed, Puerto Rico. (March 2017) - Smith, Amelia; Yee, Susan H.; Russell, Marc; Awkerman, Jill; Fisher, William S.
Abstract: Policies to protect coastal resources may lead to greater social, economic, and ecological returns when they consider potential co-benefits and trade-offs on land. In Guánica Bay watershed, Puerto Rico, a watershed management plan is being implemented to restore declining quality of coral reefs due to sediment and nutrient runoff. However, recent stakeholder workshops indicated uncertainty about benefits for the local community. A total of 19 metrics were identified to capture stakeholder concerns, including 15 terrestrial ecosystem services in the watershed and 4 metrics in the coastal zone. Ecosystem service production functions were applied to quantify and map ecosystem service supply in 1) the Guánica Bay watershed and 2) a highly engineered upper multi-watershed area connected to the lower watershed via a series of reservoirs and tunnels. These two watersheds were compared to other watersheds in Puerto Rico. Relative to other watersheds, the Upper Guánica watershed had high air pollutant removal rates, forest habitat area, biodiversity of charismatic and endangered species, but low farmland quality and low sediment retention. The Lower Guánica watershed had high rates of denitrification and high levels of marine-based recreational and fishing opportunities compared to other watersheds, but moderate to low air pollutant removal, soil carbon content, sediment and nutrient retention, and terrestrial biodiversity. Our results suggest that actions in the watershed to protect coral reefs may lead to improvements in other ecosystem services that stakeholders care about on land. Considering benefits from both coastal and terrestrial ecosystems in making coastal management decisions may ultimately lead to a greater return on investment and greater stakeholder acceptance, while still achieving conservation goals.